Molecular Beams and Model Catalysis: Activity and Selectivity of Specific Reaction Centers on Supported Nanoparticles - Libuda, Jörg (ChemPhysChem, 2004)
Reaction kinetics on nanometer-scale particles are different from those on extended surfaces of bulk materials. This fact has been utilized for a long time to empirically maximize the performance of heterogeneous catalysts, but the understanding of the underlying effects is poor at the microscopic level. Modern molecular-beam-based methods, however, allow us to derive very detailed kinetic information on catalytically active surfaces. In combination with structurally highly controlled model catalysts, microscopic insights into the activity and selectivity of specific reaction centers on catalyst nanoparticles can be obtained. This combined approach is illustrated through simple model reactions.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.ppc20.molecu
Keywords: Heterogeneous catalysis; Kinetics; Molecular beams; Nanostructures; Surface chemistry